Manajemen Kurikulum di Sekolah Berasrama (Studi Multi Kasus di SMP GIBS dan SMAS GIBS) - Irwanto, Randi Ahmad; Aslamiah, Aslamiah; Ngadimun, Ngadimun (LP. Ma'arif Janggan Magetan, 2024)
The urgency of curriculum in boarding schools is very important in realizing the effectiveness of education. Boarding education has a big role in teaching the values of discipline and independence. Educators and education units develop a curriculum that is in accordance with the conditions and needs, so that students can develop better knowledge and skills. Among the excellent boarding schools in Barito Kuala district are SMP GIBS and SMAS GIBS. Both are A-accredited schools that have implemented the 2013 curriculum and Merdeka curriculum since July 2022 at the same time. Based on interviews with teachers and education personnel, SMP GIBS and SMAS GIBS have achieved many achievements in both academic and non-academic fields with a quality learning system and complete facilities. This study aims to describe the analysis of curriculum needs, describe curriculum planning, explore curriculum implementation, and analyze curriculum evaluation at SMP GIBS and SMAS GIBS. This research is a descriptive qualitative research with a multi-case study approach. The sampling technique in this study used purposive sampling technique. Data were collected through observation techniques, in-depth interviews, and documentation. The data analysis technique was carried out with a single case analysis consisting of data reduction, data presentation, and conclusion drawing/verification as well as cross-case analysis. While the validity of the data was checked using the technique of broadening perception, increasing persistence, and triangulation. The results showed that curriculum needs analysis, curriculum planning, curriculum implementation, and curriculum evaluation at SMP GIBS and SMAS GIBS are well prepared using complete data, in accordance with the conditions and needs of students, at the right time, and involve many parties both internal and external according to their respective duties, responsibilities, and interests. Thus, good curriculum management in boarding schools is achieved, resulting in good quality education.